2019
DOI: 10.1097/ncc.0000000000000740
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Logotherapy on Distress, Depression, and Demoralization in Breast Cancer and Gynecological Cancer Patients

Abstract: Background Globally, cancer is the second leading cause of death. Breast cancer and gynecological cancer can damage patients’ body image and lead to psychological distress, depression, and demoralization syndrome. No studies have explored the effect of logotherapy in gynecological cancer patients’ psychological distress, depression, and demoralization. Objective To evaluate the effects of logotherapy on distress, depression, and demoralization in breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The reliability of the instrument was 0.86 using Cronbach's alpha (4). Moreover, in other studies, the reliability was determined to be 77% (22) and 94% (23) using the test-retest method (Figure 1).…”
Section: Instrumentsmentioning
confidence: 84%
See 2 more Smart Citations
“…The reliability of the instrument was 0.86 using Cronbach's alpha (4). Moreover, in other studies, the reliability was determined to be 77% (22) and 94% (23) using the test-retest method (Figure 1).…”
Section: Instrumentsmentioning
confidence: 84%
“…The study population was all caregivers of hemodialysis patients at the Bouali hospital in Qazvin. Based on previous studies (22) and the following formula, the sample size for this study was estimated to be 41 subjects. By considering a 20% attrition rate, a total of 50 participants in each group (intervention and control) were enrolled in the study.…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…14,22 So as cancer has been linked to many psychological disorders that can manifest during the therapeutic period including depression and anxiety, the medical team should try their best to relieve such stress providing a suitable tool to limit the side effects of these drugs. 23 In this observational study, we provide a comprehensive and systematic study of the use of nail polish solution to prevent taxane-induced nail changes in female patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Such evidence suggests that logotherapy can improve the meaning of life and may be effective in relieving the death anxiety caused by recurrent cancer ( 17 ). Also, it has been reported that logotherapy can reduce depression and demoralization in patients with breast and gynecological cancers ( 18 ).…”
mentioning
confidence: 99%